The Use of Biodiesel Residues for Heat Insulating Biobased Polyurethane Foams - Nihan Özveren; M. Özgür Seydibeyoğlu (International Journal of Polymer Science)
The commercial and biobased polyurethane foams (PUF) were produced and characterized in this study. Commercial polyether polyol, crude glycerol, methanol-free crude glycerol, and pure glycerol were used as polyols. Crude glycerol is byproduct of the biodiesel production, and it is a kind of biofuel residue. Polyol blends were prepared by mixing the glycerol types and the commercial polyol with different amounts, 10 wt%, 30 wt%, 50 wt%, and 80 wt%. All types of polyol blends were reacted with polymeric diphenyl methane diisocyanates (PMDI) for the production of rigid foams. Thermal properties of polyurethane foams are examined by thermogravimetric analysis (TGA) and thermal conductivity tests. The structures of polyurethane foams were examined by Fourier Transformed Infrared Spectroscopy (FTIR). Changes in morphology of foams were investigated by Scanning Electron Microscopy (SEM). Mechanical properties of polyurethane foams were determined by compression tests. This study identifies the critical aspects of polyurethane foam formation by the use of various polyols and furthermore offers new uses of crude glycerol and methanol-free crude glycerol which are byproducts of biodiesel industry.